Evaluasi Tenaga Pendidik di Sekolah Penyelenggara Pendidikan Inklusi Kota Batu - Ansory, Ichsan; Herviani, Vivi Kurnia; Amelia, Delora Jantung (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
ABSTRACT The implementation of inclusive education has been implemented in most districts/cities in Indonesia, one of which is in the city of Batu. Batu City cares about the education and development of students with special needs as seen in the launch of an inclusive education program. In this regard, this study aims to evaluate the educators of schools providing inclusive education in Batu City based on the Guidelines for the Implementation of Inclusive Education by the PKLK Directorate in 2011. The research design used in this study was an evaluative study with a qualitative approach. Most of the educators in the two inclusive education schools in Batu City have qualified as special educators, because they have an extraordinary education background. Two schools have one special supervisor each. The recruitment of special educators carried out by both schools is in accordance with the guidelines because they can recruit and submit to the Education Office, while the availability of special educators in one school is still not balanced with the number of GDPK that is available. accepted in school, therefore the handling for PDBK by GPK is still not optimal due to limited teaching time.